2020
DOI: 10.1007/s10803-020-04498-0
|View full text |Cite
|
Sign up to set email alerts
|

SOLACE: A Psychosocial Stigma Protection Intervention to Improve the Mental Health of Parents of Autistic Children—A Feasibility Randomised Controlled Trial

Abstract: This study presents findings from a feasibility trial, testing an 8-week psychosocial stigma protection intervention (SOL-ACE) designed to improve the mental health of parents of autistic children. Seventeen parents were stratified then randomly assigned to either SOLACE (n = 9) or control group (n = 8). Retention and adherence rates were excellent with minimal missing data suggesting SOLACE had good acceptability and feasibility. Quantitative analysis revealed that mental health scores had significantly impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 87 publications
0
14
0
4
Order By: Relevance
“…Various interventions to promote wellbeing in parents of children with ASD have been done around the world but hardly in developing countries. Some involved spirituality [ 49 ] or multi component involving psycho education, cognitive restructuring strategies and compassion focused methods to help parents cope with, prevent, and reduce the harmful effects of self-stigma and eventually improve their mental health [ 50 ]. Varying degrees of success were recorded with implications for scaling.…”
Section: Discussionmentioning
confidence: 99%
“…Various interventions to promote wellbeing in parents of children with ASD have been done around the world but hardly in developing countries. Some involved spirituality [ 49 ] or multi component involving psycho education, cognitive restructuring strategies and compassion focused methods to help parents cope with, prevent, and reduce the harmful effects of self-stigma and eventually improve their mental health [ 50 ]. Varying degrees of success were recorded with implications for scaling.…”
Section: Discussionmentioning
confidence: 99%
“…Every session had a ‘core topic’ and finished with ‘free sharing time’ during which parents were encouraged to ask or share topics of their choice. A brief overview of the sessions is provided in Table 1 , and a more detailed description of the intervention development is published elsewhere ( Lodder et al, 2020 ). The intervention manual is available from the author.…”
Section: Methodsmentioning
confidence: 99%
“…The results of this pilot trial showed that the participants who took part in SOLACE reported significant improvements in their mental health compared to those allocated to the control group. The underpinning theoretical development and intervention mechanisms of SOLACE, including its preliminary effectiveness in relation to all measured outcomes (courtesy and affiliate stigma; self-esteem; self-compassion, positive meaning of caregiving; self-blame; social support; and social isolation) are reported elsewhere ( Lodder et al, 2019b , Lodder et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interventions that encourage and provide opportunities for physical, sensory and emotional regulation (e.g., sensory integration therapy, Randell et al, 2019 ) are compatible with this stance. Interventions can promote an understanding of autism and neurodiversity in people in the child's world, such as caregivers (e.g., EMPOWER-ASD intervention, 2 Systemic Autism-related Family Enabling intervention, McKenzie et al, 2019 ; SOLACE programme, Lodder et al, 2020 ), and education professionals and peers (e.g., Learning about Neurodiversity at School project 3 ). These interventions also support non-autistic people to build resilience, develop a positive philosophy toward the autistic child, and to build relationships in a respectful, supportive and harmonious manner.…”
Section: Implications For Early Autism Interventionmentioning
confidence: 99%